The training of doctoral tutors as an academic option of the contemporary Cuban medical university - José Miguel Rodríguez Perón (Revista Cubana de Medicina Militar)
The historical analysis of the doctoral training process in the field of Medical and Health Sciences in Cuba allows us to argue that the customary way of executing the tutoring of doctoral students results from the experience obtained in the exercise and practice of this activity in over time. Infrequently, potential tutors receive some training about the mentoring process, so they lack the necessary tools to face the challenges of the process and meet successful professional performance. Therefore, the proposal of programs is a necessity based on reflection about national and foreign tutorial practice and establishing tools aimed at perfecting the professional development of the tutors in the training of doctors. For all the aforementioned, and in view of the questions about the suitability and competences of the doctoral tutor, the objective of the article is to argue about the benefits of the design and implementation of training programs for tutors in Biomedical Sciences as a methodological strategy to strengthen their preparation, enhance the scientific production of doctoral students and raise the quality of training for future researchers.